Cognitive Decline in Older Persons Initiating Anticholinergic Medications - Shah, Raj C. (Public Library of Science, 2013)
BACKGROUND: This study examines the effect of initiating medications with anticholinergic activity on the cognitive functions of older persons. METHODS: Participants were 896 older community-dwelling, Catholic clergy without baseline dementia. Medication data was collected annually. The Anticholinergic Cognitive Burden Scale was utilized to identify use of a medication with probable or definite anticholinergic activity. Participants had at least two annual cognitive evaluations. RESULTS: Over a mean follow-up of 10 years, the annual rate of global cognitive function decline for never users, prevalent users, and incident users was −0.062 (SE = 0.005), −0.081(SE = 0.011), and −0.096 (SE = 0.007) z-score units/year, respectively. Compared to never users, incident users had a more rapid decline (difference = −0.034 z-score units/year, SE = 0.008, p<0.001) while prevalent users did not have a significantly more rapid decline (p = 0.1). CONCLUSIONS: Older persons initiating a medication with anticholinergic activity have a steeper annual decline in cognitive functioning than those who are not taking these medications.